Antiplasmodial and Cytotoxic Activities of Extract and Compounds from Ozoroa obovata (Oliv.) R. & A. Fern. var. obovata. Issue 8 (17th June 2021) - Tajuddeen, Nasir; Swart, Tarryn; Hoppe, Heinrich C.; van Heerden, Fanie R.
Abstract: Ozoroa obovata (Oliv.) R. & A. Fern. var. obovata found in KwaZulu‐Natal in South Africa was investigated for phytochemical constituents, and for antiplasmodial and cytotoxic effects. The plant leaves were collected from the University of KwaZulu‐Natal (UKZN) arboretum on the Pietermaritzburg Campus, in March 2019. The inhibitory activity against 3D7 Plasmodium falciparum was determined using the parasite lactate dehydrogenase (pLDH) assay and cytotoxicity against HeLa cells was evaluated using the resazurin assay. The bioactive compounds were isolated by chromatographic purification and their structures were established with spectroscopic and spectrometric techniques. The plant leaf extract displayed significant antiplasmodial activity at 50 μg/mL and was also cytotoxic against HeLa cells. Chromatographic purification of the extract led to the isolation of two biflavonoids, four flavonoid glycosides, a steroid glycoside, and a megastigmene derivative. The compounds displayed antiplasmodial and antiproliferative activities at 50 μg/mL but the activity was substantially reduced at 10 μg/mL. The activities and compounds are being reported in O. obovata for the first time. Abstract :